COMPARISON BETWEEN YII FRAMEWORKS AND LARAVEL IN 3 DIFFERENT VERSION FOR VIEWING LARGE DATA OF SHIPYARD INDUSTRY IN INDONESIA - Ummi Khaira Latif; Tien Fabrianti Kusumasari (School of Industrial and System Engineering, Telkom University, 2018)
The objective of this paper is to compare two PHP frameworks with execution time, peak memory usage and throughput metrics. This performance comparison was done for Laravel and Yii2 frameworks using MySQL employee database [26] which freely downloaded for testing necessary. The database provided a large amount of data included million entry records. Using a large amount of record, we try to give some view to another developer for considering when choosing the PHP framework for their development. The result in this paper give Laravel has better performance in execution time and throughput measurement but not in memory usage. This result can be affected by many factors including the testing environment in when comparison process implementation. Keywords—Laravel, Yii2, PHP Framework, Performance Comparison.